Primary hemostasis in children with cirrhosis prior to liver transplantation: key roles of liver disease severity, von Willebrand factor, and platelet count - Dievoet, Marie–Astrid van; Baaten, Constance C.F.M.J.; Nagy, Magdolna; David, Clara; Brusa, Davide; Dahlqvist, Géraldine; Coubeau, Laurent; De Bruyne, Ruth; Jannone, Giulia; Scheers, Isabelle; Hermans, Cedric; Tambucci, Roberto; et al. (Journal of thrombosis and haemostasis, 2025)
Thrombocytopenia is common in pediatric patients with cirrhosis, but the extent and relevance of functional platelet defects remain unclear. This proof-of-principle study aimed to characterize platelet properties in cirrhotic children before living-donor liver transplantation using state-of-the-art platelet-based assays, hypothesizing that primary hemostasis in this group is well preserved. From January 2022 to July 2023, pediatric cirrhotic patients were prospectively enrolled 1 day before liver transplantation. An age-matched control group was included. Platelet functionality was assessed using flow cytometry and microfluidic assays, along with plasma proteins including von Willebrand factor (VWF), a disintegrin and metalloproteinase with a thrombospondin type 13, and soluble glycoprotein VI. A subset of patients was also re-evaluated 3 months after transplant. Twenty-seven pediatric cirrhotic patients, primarily with cholestatic liver disease, and 15 controls were enrolled. Patients had pediatric end-stage liver disease scores from −10 to 44. Flow cytometry revealed subtle platelet activation in the absence of agonists and reduced activation with high agonist concentrations. Microfluidic assays revealed variations in platelet thrombus formation among the patients, identifying 2 distinct subgroups: 1 with severe liver disease and higher platelet counts, showing preserved primary hemostasis, and another with lower platelet count and moderate platelet thrombus impairment. High VWF levels likely compensated for reduced platelet activation under high shear. Two subgroups with differences in platelet thrombus formation under flow were identified pretransplantation, likely depending on severity of liver disease, platelet count, and VWF levels. Whether the need for platelet intervention is different between these subgroups requires further clinical investigation. [Display omitted]